Pergamon – Die Arbeiten in der Kampagne 2021 - Pirson, Felix (Archäologischer Anzeiger, 2022)
In 2021, the Pergamon Excavation concentrated on projects in the framework of the new research programme TransPergMikro. The dating of the ›Goths’ Wall‹ to the 3rd cent. A.D. was securely confirmed. The discovery and documentation of an imperial-period peristyle building east of the Red Hall contribute further to our understanding of the urban development. The now completed investigations of the amphitheatre and the theatre on Musalla Mezarlığı resulted in some surprising findings concerning the origin, structure und appearance of these large-scale edifices. With the ›Lower Western Gymnasium‹ another major structure from the imperial period was documented. Geophysical prospection in the area of the Asklepieion yielded new evidence on the extent and limits of urbanization. Excavation of an imperial-period funerary monument northwest of the sanctuary furnished further, significant evidence relating to the funerary culture of Pergamon’s imperial-period elites. The survey in the micro-region concentrated on the transition zone of the eastern foothills of the Kara Dağ peninsula and the adjoining western Bakırçay plain. Alongside the diachronic reconstruction of land use, several settlement sites were documented for the first time. They include a presumed Achaemenid dynastic residence, Hellenistic fortifications with boundary markers, and another imperial-period villa with extensive late antique to early Byzantine ceramic production. The rescue excavation of Ballık cave, discovered the previous year, was able to confirm the temporary presence of Epipalaeolithic hunters and gatherers as well as the later use of the site as a sanctuary of Meter. The investigations of sediment archives in Pergamon and the river plain using physical geography methods were continued. Monument conservation measures focused on the east wall of the Great Gymnasium, the theatre terrace and the Lower Rotunda in the Asklepieion as well as on the stabilization of a Hellenistic wall decoration in the incrustation style.